EVALUATING THE EFFECTIVENESS OF TRAINING AND DEVELOPMENT INITIATIVES ON EMPLOYEE RETENTION AND JOB SATISFACTION IN INDIAN PUBLIC SECTOR BANKS - Singh, Abhishek Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This is a study that will evaluate the effects of a training and development program on work satisfaction and staff retention in the Indian public sector banks using secondary data that has been collected in previous studies. With a quantitative type of analysis, the paper assesses the correlation amid job satisfaction and retention intention, training quality, career development, skill improvement, and organizational support through such measures as descriptive statistics, chi-square, t-tests, MANOVA, principal component analysis, and regression models. The findings indicate that training and development programs intend to emphasize career development opportunities, improvement of skills, and support within organizations, which have a profound influence over work satisfaction and retention. Demographic factors such as gender or level of income had no significant effect on the training impressions, and this means that the positive results of the policy were obtained with an equal level of success in all categories of employees. The research contributes to knowledge through providing evidence-based knowledge on how organized need-based training programs can increase employee engagement, skills, and stability of an organization within competitive environments such as the banking industry. These results have significant HR policy implications for the banks in the public sector.